Curriculum development - Bilbao, Purita P.; Lucido, Paz I.;Iringan, Tomasa C.;Javier, Rodrigo B. (Quezon City, Philippines : Lorimar Publishing Company Inc., 2008)
Curriculum development is an instructional material in module which complements the 3- unit course of the New Teacher Education Curriculum. It closely approximates the syllabus of the course on curriculum development as prescribed by CMO 30-s 2004.
Module 1. Curriculum: concepts, nature and purposes -- Module 2. Crafting the curriculum -- Module 3. Implementing the curriculum -- Module 4. assessing the curriculum -- Module 5. Addressing the future: curriculum innovations.
Includes bibliographical references.
Keywords: CURRICULUM PLANNING -- PHILIPPINES